Insulated coated wire, coil, and magnetic component

By using insulating layers of Si, Ti and oxygen in the insulating wire of electronic components and firing to form an inorganic insulating layer at high temperature, the problem of loss of insulation at high temperature is solved, and high heat resistance of the wire and stability of the inductance are achieved.

CN119895503APending Publication Date: 2025-04-25TDK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380066659.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-30
Filing Date
2023-11-29
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Insulated-covered wires in existing electronic components tend to lose their insulation at high temperatures, resulting in short circuits between windings in the coils, affecting the stability of the inductance.

Method used

An insulating layer including Si, Ti and oxygen is used, and the ratio of the Ti content in the insulating layer to the total content of Si and Ti is 2.5 at % or more and 50 at % or less. The insulating layer is formed by the sol-gel method, and the insulating layer is fired at a high temperature to form an inorganic insulating layer.

Benefits of technology

It realizes the insulation of the conductor at high temperature, prevents short circuits between windings, and improves the heat resistance of the coil and the stability of the inductance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895503A_ABST
    Figure CN119895503A_ABST
Patent Text Reader

Abstract

An insulated coated wire has a metal conductor part containing Cu, and an insulating layer covering the metal conductor part. The insulating layer in the insulating coated wire contains Si, Ti, and oxygen, and the ratio of the Ti content in the insulating layer to the total content of Si and Ti is 2.5 at% or more and 50 at% or less. A coil has a conductive wire including a metal conductor portion containing Cu, and an insulating layer or an inorganic insulating layer covering the metal conductor portion. An insulating layer in the coil contains an organic material containing one or more inorganic elements M selected from the group consisting of Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni, and Mg. An inorganic insulating layer in the coil contains an oxide containing an inorganic element M.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a conductive wire with an insulating coating, a coil, and a magnetic component including the coil. Background Art

[0002] In electronic components such as inductors, transformers, and choke coils, a conductive wire having an insulating coating is used as a material for the coil. In such electronic components, the insulating coating of the conductive wire has the function of ensuring insulation between windings in the coil. In existing electronic components, conductive wires having an insulating coating formed of a resin such as a polyamide-imide resin, a polyimide resin, an epoxy resin, or a polyurethane resin are generally used. For example, Patent Document 1 discloses a conductive wire having an insulating coating formed of an epoxy resin, and Patent Document 2 discloses a conductive wire having an insulating coating formed of a copolyamide resin.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 2890280

[0006] Patent Document 2: Japanese Patent Application Laid-Open No. 3-089414 Summary of the invention

[0007] The present disclosure provides an insulated coated conductive wire having high heat resistance, a coil having high heat resistance, and a magnetic component including the coil.

[0008] In the insulated covered conductor according to the first aspect of the present disclosure,

[0009] The invention comprises: a metal conductor part containing Cu, and an insulating layer covering the metal conductor part.

[0010] The insulating layer contains Si, Ti and oxygen,

[0011] A ratio of a Ti content in the insulating layer to a total content of Si and Ti is 2.5 at % or more and 50 at % or less.

[0012] In the insulated covered conductor according to the second aspect of the present disclosure,

[0013] The invention comprises: a metal conductor part containing Cu, and an inorganic insulating layer covering the metal conductor part.

[0014] The inorganic insulating layer comprises an oxide containing Si and Ti,

[0015] A ratio of a Ti content in the inorganic insulating layer to a total content of Si and Ti is 2.5 at % or more and 50 at % or less.

[0016] In the coil according to the third aspect of the present disclosure,

[0017] A conductive wire comprising: a metal conductive portion containing Cu and an insulating layer covering the metal conductive portion;

[0018] The insulating layer includes an organic substance containing one or more inorganic elements M selected from the group consisting of Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni, and Mg.

[0019] In the coil according to the fourth aspect of the present disclosure,

[0020] A conductive wire comprising: a metal conductive portion containing Cu and an inorganic insulating layer covering the metal conductive portion;

[0021] The inorganic insulating layer includes an oxide containing one or more inorganic elements M selected from the group consisting of Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni, and Mg.

[0022] The magnetic component according to the present disclosure includes the coil according to the third aspect or the fourth aspect and a magnetic core made of a soft magnetic material.

[0023] The coil is buried inside the magnetic core. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a cross-sectional view showing an insulated covered conductive wire according to one embodiment of the present disclosure.

[0025] Figure 2 It is a cross-sectional view showing an insulation coated conductor having an inorganic insulation layer after firing.

[0026] Figure 3 It means using Figure 1 as well as Figure 2 A perspective view of an example of a coil of insulating coated conductive wire is shown.

[0027] Figure 4 Yes means including Figure 3 1 is a cross-sectional view showing an example of an electronic component of a coil shown in FIG. 2 is a cross-sectional view showing a modified example of an insulating coated conductor.

[0028] Figure 5A It is a cross-sectional view showing a modified example of the insulating covered conductive wire.

[0029] Figure 5B It is a cross-sectional view showing another modified example of the insulating covered conductive wire.

[0030] Figure 6 It means using Figure 5AA perspective view of an example of a coil of insulating coated conductive wire is shown.

[0031] Explanation of symbols

[0032] 2, 2α, 2β...Insulated coated wire (conductor)

[0033] 2s...most surface

[0034] 2e1, 2e2, ... end

[0035] 6……Metal conductor part

[0036] 6a……Main body

[0037] 6b...Metal cladding

[0038] 8...Insulation layer (insulation coating)

[0039] 8A...Unfired insulation layer

[0040] 8B...Inorganic insulation layer

[0041] 20, 20α... coil

[0042] 100……Electronic components (magnetic components)

[0043] 40... Magnetic core DETAILED DESCRIPTION

[0044] Hereinafter, an embodiment of the present disclosure will be described with reference to the accompanying drawings. The embodiment of the present disclosure described below is for the purpose of illustrating an example of the present disclosure. Various components involved in the embodiment of the present disclosure, such as numerical values, shapes, materials, manufacturing processes, etc., can be changed or altered within the scope that does not cause technical problems. In addition, the shapes shown in the drawings of the present disclosure may not be consistent with the actual shapes, etc. This is because the shapes, etc. are sometimes changed for the purpose of explanation.

[0045] (First Embodiment)

[0046] The insulated coated wire 2 of this embodiment is a wire having a metal conductor 6 and an insulating layer 8 covering the metal conductor 6. The cross-sectional shape of the insulated coated wire 2 is not particularly limited, and the insulated coated wire 2 may also have a circular, elliptical, rectangular, square, or other polygonal cross-sectional shape. Figure 1 and Figure 2 In the round-wire-shaped insulated coated wire 2 shown, the metal conductor portion 6 has a circular cross-sectional shape. Figure 1 and Figure 2 Each of the drawings illustrates a cross section perpendicular to the longitudinal direction (Y-axis direction) of the insulated coated conductor 2 , and the X-axis, Y-axis, and Z-axis in each drawing are perpendicular to each other.

[0047] The average diameter D of the metal conductor portion 6 can be Figure 1 and Figure 2 The measurements are made on the cross section shown. Figure 1 and Figure 2 In the case of the round-shaped insulating coated wire 2 shown, for example, the average diameter D of the metal conductor portion 6 is preferably 0.1 mm or more and 1.5 mm or less. In addition, the range of the average diameter D illustrates a preferred size range when the insulating coated wire 2 is applied to a coil such as an inductor, and the size of the metal conductor portion 6 is not necessarily limited to the above size range in any application.

[0048] The metal conductor part 6 is a part through which the current flows, and plays a central role in the insulating coated wire 2. Therefore, the metal conductor part 6 is composed of a metal component, including at least Cu. For example, the metal conductor part 6 may also be pure copper or a copper alloy. The detailed composition of the metal conductor part 6 is not particularly limited, but preferably, Cu is the main component that accounts for at least 50wt% of the metal conductor part 6, and the content of Cu in the metal conductor part 6 is more preferably 70wt% or more. In the case where the metal conductor part 6 is a copper alloy, in addition to Cu, the metal conductor part 6 may also contain one or more elements selected from Ag, Ni, Al, Zn, Be, Sn and Mn. The composition of the metal conductor part 6 can be analyzed, for example, by energy dispersive X-ray analysis (EDS) or wavelength dispersive X-ray analysis (WDS).

[0049] The insulating layer 8 is a coating made of an insulating material covering the metal conductor part 6. The coverage of the insulating layer 8 relative to the surface of the metal conductor part 6 is preferably 90% or more, and more preferably 100%. Figure 1 and Figure 2 The calculation can be performed based on the cross section perpendicular to the length direction of the insulating coated wire 2. The insulating layer 8 is located at the outermost side of the insulating coated wire 2, and the surface of the insulating layer 8 constitutes the outermost surface 2s of the insulating coated wire 2.

[0050] The average thickness T of the insulating layer 8 Ave When the insulated coated conductor 2 is used for a coil such as an inductor, the average thickness T of the insulating layer 8 is 200 mm / s. Ave The average thickness T is preferably 1 μm or more and 220 μm or less, and more preferably 1 μm or more and 200 μm or less. Ave By setting the above range, the insulation resistance between the windings can be maintained high and the increase of magnetic flux leakage can be suppressed. The variation of the thickness t of the insulating layer 8 is preferably within the range of the average thickness T Ave The average thickness T AveIn other words, the tolerance of the thickness t of the insulating layer 8 is preferably within the range of ±10%, more preferably within the range of ±5%.

[0051] When calculating the average thickness T of the insulating layer 8 Ave When the insulation layer 8 is used as the insulating layer 8, it is preferred to analyze at least 10 cross sections of the insulating coated conductor 2, and preferably measure the thickness t of at least 10 cross sections of the insulating layer 8. In addition, the maximum thickness t of the insulating layer 8 can be determined by the measurement. MAX and minimum thickness t MIN , based on T Ave ,t MAX and t MIN The tolerance (%) of the thickness t of the insulating layer 8 can be calculated. Specifically, t MAX Relative to T Ave Deviation (t MAX -T Ave ) and t MIN Relative to T Ave Deviation (t MIN -T Ave ), divide the deviation with the larger absolute value by T Ave , and calculate the thickness tolerance. That is, calculate "F1=(|t MAX -T Ave | / T Ave )×100” and “F2=(|t MIN -T Ave | / T Ave )×100”, the larger of F1 and F2 is used as the tolerance (%) of thickness t.

[0052] The insulating layer 8 contains at least Si, Ti and oxygen. In addition, the ratio of the Ti content in the insulating layer 8 to the total content of Si and Ti (Ti / (Si+Ti)) is 2.5 at% to 50 at%, more preferably 5.0 at% to 40 at%, and further preferably 7.5 at% to 25 at%. As described above, by setting the Ti / (Si+Ti) ratio in the insulating layer 8 to 2.5 at% to 50 at%, the variation in the thickness of the insulating layer 8 can be reduced, and high heat resistance can be obtained.

[0053] The insulating layer 8 is preferably formed by a sol-gel method. When the insulating layer 8 is formed by the sol-gel method, the specifications (size and material, etc.) of the metal conductor portion 6 remain unchanged before and after firing, but the state of the insulating layer 8 changes. In the present embodiment, the insulating layer 8 before firing is referred to as "unfired insulating layer 8A", and the insulating layer 8 after firing is referred to as "inorganic insulating layer 8B". Both the unfired insulating layer 8A and the inorganic insulating layer 8B satisfy 2.5at%≤(Ti / (Si+Ti))≤50at%. The unfired insulating layer 8A is a coating containing organic matter, but in contrast, the inorganic insulating layer 8B is a coating of an oxide that does not substantially contain organic matter. Below, the characteristics of the unfired insulating layer 8A and the inorganic insulating layer 8B are described in detail together with an example of a method for forming the insulating layer 8.

[0054] When the insulating layer 8 is formed by the sol-gel method, first, a liquid Si source and a liquid Ti source are mixed to prepare a coating liquid.

[0055] The Si source used in the coating solution is not particularly limited, for example, alkoxysilane is preferably used. As alkoxysilane, monoalkoxysilane, dialkoxysilane, trialkoxysilane, tetraalkoxysilane can be exemplified. As monoalkoxysilane, trimethylmethoxysilane, trimethylethoxysilane, trimethyl (phenoxy) silane, etc. can be exemplified. As dialkoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, diisobutyldimethoxysilane, tert-butylmethyldimethoxysilane, tert-butylmethyldiethoxysilane, etc. can be exemplified. As trialkoxysilane, trimethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, methyltrimethoxysilane, n-propyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, phenyltrimethoxysilane, etc. can be exemplified. Examples of the tetraalkoxysilane include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetraisopropoxysilane, etc. As the Si source, one type of alkoxysilane may be used, or two or more types of alkoxysilanes may be used in combination.

[0056] The Ti source used in the coating solution is not particularly limited, for example, titanium alkoxide or titanium chelate is preferably used. As titanium alkoxide, titanium tetramethoxide, titanium tetraethoxide, titanium tetra-n-propoxide, titanium tetraisopropoxide, titanium tetra-n-butoxide, etc. can be exemplified. As titanium chelate, titanium acetylacetonate, titanium tetraacetylacetonate, titanium ethyl acetoacetate, titanium octanediol, ammonium lactate titanium, titanium lactate, triethanolamine titanium, etc. can be exemplified. As the Ti source, one titanium alkoxide or titanium chelate can be used, or two or more titanium alkoxides or / and titanium chelates can be used.

[0057] The Ti / (Si+Ti) ratio in the insulating layer 8 can be controlled by the ratio of the Si source to the Ti source in the coating solution. In addition, in order to adjust the viscosity of the coating solution, in addition to the Si source and the Ti source, an organic solvent can be appropriately added to the coating solution. In this case, the organic solvent used is not particularly limited. For example, ethanol, n-propanol, isopropanol, acetone or methyl ethyl ketone can be used as the organic solvent.

[0058] Next, the unfired insulating layer 8A is formed by a dip coating method using the above-mentioned coating liquid. Specifically, in the dip coating method, a wire consisting only of the metal conductor portion 6 is immersed in the above-mentioned coating liquid, and then the wire taken out of the coating liquid is dried. As the wire consisting only of the metal conductor portion 6 before being immersed in the coating liquid, a wire manufactured by a known method can be prepared. In addition, the process of immersing the wire in the coating liquid can be implemented multiple times. The thickness tA of the unfired insulating layer 8A can be controlled by the immersion time in the coating liquid and the number of immersions in the coating liquid. For example, the immersion time in the coating liquid can be set to 1 second to 300 seconds, and the number of immersions in the coating liquid can be set to 1 time to 10 times.

[0059] In addition, when multiple immersion steps are performed, a drying process may be performed after each immersion, and the drying process conditions are not particularly limited. For example, the drying temperature for each time may be set to 50° C. or more and less than 300° C., and the heat drying time for each time may be set to 0.5 to 3 hours.

[0060] By the above-mentioned dip coating method, the unfired insulating layer 8A is formed on the surface of the metal conductor portion 6. The method for forming the unfired insulating layer 8A is not limited to the dip coating method, and other forming methods such as the spray coating method may be adopted.

[0061] The unfired insulating layer 8A after drying ( Figure 1 ) is a coating of a dry gel containing organic matter such as a polymer compound derived from a Si source and a Ti source. It is believed that the molecular structure of the organic matter contained in the unfired insulating layer 8A varies depending on the type of Si source and Ti source used in the coating solution and the degree of drying. The structural analysis of the organic matter contained in the unfired insulating layer 8A is sometimes difficult, and the molecular structure is not particularly limited, but the organic matter in the unfired insulating layer 8A contains at least Si and Ti. In addition, the organic matter in the unfired insulating layer 8A contains C (carbon), H (hydrogen) and O (oxygen) which are general constituent elements of organic matter.

[0062] Here, "organic matter containing Si and Ti" refers to an organic compound containing bonding via Si and bonding via Ti in the molecular chain. As bonding via Si, for example, Si-O, Si-H, Si-OH, Si-OR (R is an organic functional group) and the like can be cited. Similarly, as bonding via Ti, for example, Ti-O, Ti-H, Ti-OH, Ti-OR and the like can be cited. As mentioned above, the structural analysis of the organic matter in the unfired insulating layer 8A is not easy, so the bonding via Si and the bonding via Ti are not particularly limited, but it is considered that at least Si-O and Ti-O are contained in the organic matter of the unfired insulating layer 8A.

[0063] The unfired insulating layer 8A may also contain oxides generated by decomposition of a portion of the organic matter. That is, the unfired insulating layer 8A may also be a composite containing organic matter and inorganic matter. Examples of oxides generated by decomposition of organic matter include SiO2, TiO2, and Si-Ti-O (composite oxide containing Si and Ti).

[0064] As described above, it is considered that Si and Ti exist in the skeleton of the polymer compound in the unfired insulating layer 8A, and a part of Si and Ti may exist as oxides. The Ti / (Si+Ti) ratio in the unfired insulating layer 8A is 2.5 at% or more and 50 at% or less, more preferably 5.0 at% or more and 40 at% or less, and further preferably 7.5 at% or more and 25 at% or less.

[0065] The Si content (at%), Ti content (at%) and Ti / (Si+Ti) ratio in the unfired insulating layer 8A can be calculated by, for example, point analysis using EDS or WDS. The point analysis of EDS or WDS is preferably performed at least at 10 locations, and the average value thereof is calculated. If the total of the elements detected by the point analysis is set to 100 at%, the total content of Si and Ti in the unfired insulating layer 8A is not necessarily limited, but is preferably, for example, 1 at% or more and 10 at% or less.

[0066] The unfired insulating layer 8A contains C and H, but these elements disappear during the firing process described later. Among the elements contained in the unfired insulating layer 8A, the content ratio RO of the elements that disappear due to firing is preferably greater than 75wt% and less than 90wt%. The content ratio RO in the unfired insulating layer 8A can be calculated using a differential thermal / thermogravimetric simultaneous measurement device (TG-DTA). Specifically, in the analysis by TG-DTA, a measurement sample selected from the insulated coated conductor 2 having the unfired insulating layer 8A is heated to 700°C at a certain temperature increase rate. Based on the weight change of the measurement sample at this time, the content ratio RO of the elements burned during firing can be calculated.

[0067] In addition, the unfired insulating layer 8A may contain one or more elements selected from B, Al, Zn, P, Ta, Nb, Bi, Ba, Ca, V, Ge, and Te. These elements may be intentionally added to the coating liquid or may be contained in the unfired insulating layer 8A as impurities.

[0068] The average thickness T1 of the unfired insulating layer 8A Ave Although not necessarily limited, it is preferably 1.5 μm or more and 220 μm or less. The variation of the thickness tA of the unfired insulating layer 8A is preferably within a range of the average thickness T1 Ave The average thickness is preferably within the range of ±10%, preferably within the range of ±10%, Ave In other words, the tolerance of the thickness tA of the unfired insulating layer 8A is preferably within the range of ±10%, and more preferably within the range of ±5%.

[0069] The insulated coated conductor 2 having the unfired insulating layer 8A is subjected to heat treatment (sintering treatment) under predetermined conditions to sinter the unfired insulating layer 8A, thereby obtaining Figure 2 The insulating coated conductor 2 having the inorganic insulating layer 8B is shown. The heat treatment conditions are not particularly limited. For example, the holding temperature is preferably set to 300° C. or higher and 900° C. or lower (more preferably 500° C. or higher and 900° C. or lower), and the temperature holding time is preferably set to 0.5 hours or higher and 10 hours or lower. In addition, the heat treatment may be performed in an inert atmosphere such as nitrogen.

[0070] There are organic substances containing Si and Ti in the unfired insulating layer 8A, but through the above-mentioned heat treatment, the organic substances are decomposed and oxidized to form a coating containing oxides of Si and Ti. That is, Si and Ti in the organic substances remain in the inorganic insulating layer 8B and become oxides. On the other hand, most of the elements derived from organic substances, such as carbon and hydrogen, contained in the unfired insulating layer 8A are gasified and disappear during the oxidation and / or phase change process of the unfired insulating layer 8A. For example, the carbon in the unfired insulating layer 8A becomes CO2 gas and disappears from the insulating layer. In addition, the hydrogen in the unfired insulating layer 8A becomes water vapor (H2O) and disappears from the insulating layer.

[0071] As described above, the inorganic insulating layer 8B after firing preferably contains at least oxides containing Si and Ti, and substantially contains no organic matter. The content (residual amount) of organic matter in the inorganic insulating layer 8B can be analyzed by TG-DTA. Specifically, in the analysis performed by TG-DTA, a measurement sample selected from the insulated coated wire 2 having the inorganic insulating layer 8B is heated to 700°C at a certain heating rate. Then, the content of organic matter can be calculated from the weight change of the measurement sample in the temperature range of 300°C to 700°C. For example, based on the sample weight at 300°C, when the rate of change of the sample weight in the temperature range of 300°C to 700°C is within the range of ±3% (i.e., within the range of -3% or more and +3% or less), it can be judged that the inorganic insulating layer 8B "substantially contains no organic matter".

[0072] The Ti / (Si+Ti) ratio in the insulating layer 8 hardly changes before and after firing, so the Ti / (Si+Ti) ratio in the inorganic insulating layer 8B is greater than 2.5at% and less than 50at%, more preferably greater than 5.0at% and less than 40at%, and further preferably greater than 7.5at% and less than 25at%.

[0073] In addition, the inorganic insulating layer 8B may contain other elements besides Si, Ti and oxygen. Examples of other elements include B, Al, Zn, P, Ta, Nb, Bi, Ba, Ca, V, Ge and Te. If the total content of elements except oxygen contained in the inorganic insulating layer 8B is 100 at%, the total content of Si and Ti in the inorganic insulating layer 8B is preferably 70 at% or more, and more preferably 80 at% or more.

[0074] The Si content (at%), Ti content (at%) and Ti / (Si+Ti) ratio in the inorganic insulating layer 8B can be calculated by point analysis using EDS or WDS in the same manner as the analysis of the unfired insulating layer 8A. The point analysis of EDS or WDS is preferably performed at least at 10 locations and the average value is calculated.

[0075] In addition, the inorganic insulating layer 8B is preferably a film with high density and homogeneity, rather than a morphology formed by the accumulation of granular or / and fibrous substances. For example, in the inorganic insulating layer 8B, Si and Ti are preferably uniformly distributed rather than locally unevenly distributed, and preferably the existence position of Si is repeated with the existence position of Ti. The distribution of Si and Ti in the inorganic insulating layer 8B can be confirmed, for example, by mapping analysis using EDS or WDS. In the mapping image obtained by the analysis, the concentration of the measured object element (Si, Ti) is expressed as the brightness corresponding to the integral intensity of the detection peak (the peak of the characteristic X-ray detected at each measurement point), and it is possible to visually confirm whether the measured object element is uneven. In addition, the data of the brightness or integral intensity obtained by the mapping analysis is taken as a whole, and the average value, standard deviation and coefficient of variation (standard deviation / mean value) of the whole are calculated, so that the distribution of the measured object element can be quantitatively evaluated. For example, in the inorganic insulating layer 8B, the coefficient of variation of the Si distribution and the coefficient of variation of the Ti distribution are preferably less than 0.5.

[0076] As described above, in the inorganic insulating layer 8B, the oxide containing Si and Ti is the main phase, and the main phase is preferably homogeneously dispersed. For example, the area ratio of the main phase in the inorganic insulating layer 8B is preferably 80% or more, and more preferably 90% or more. In other words, in the cross section of the inorganic insulating layer 8B, the total area ratio of phases other than the main phase is preferably 20% or less, and more preferably 10% or less. Other phases may include oxides having a composition different from that of the oxide containing Si and Ti, residual carbon, and the like. In addition, the above-mentioned area ratios can be calculated by analyzing the cross section of the inorganic insulating layer 8B using an SEM, an optical microscope, or the like, and the field of view during the cross-sectional analysis can also be set to, for example, 100×100μm. 2 ~500×500μm 2 .

[0077] The average thickness T2 of the inorganic insulating layer 8B Ave The thickness tB of the unfired insulating layer 8A is not necessarily limited, but is preferably 1 μm or more and 200 μm or less. The tolerance of the thickness tB of the unfired insulating layer 8A is preferably within a range of ±10%, and more preferably within a range of ±5%.

[0078] The use of the insulating coated wire 2 is not particularly limited, but the insulating coated wire 2 can be particularly suitably used as a coil for electronic components such as an inductor, a transformer, and a choke coil. For example, Figure 3 It is a perspective view illustrating a coil 20 formed of the insulating coated conductive wire 2 .

[0079] Figure 3 The coil 20 has a structure in which the insulating coated conductor 2 is wound in a spiral shape along the Z axis. Figure 3In the coil 20, a winding method of arranged multi-layer winding is adopted, but the winding method of the insulating coated wire 2 is not particularly limited. For example, winding methods such as one-layer arranged winding, uneven winding, oblique winding, or space winding may also be adopted. The number of turns of the insulating coated wire 2 in the coil 20 is not particularly limited and can be appropriately determined according to the desired coil characteristics. For example, the number of turns of the insulating coated wire 2 can also be set to 0.5 turns to 100 turns. In addition, when the insulating coated wire 2 is wound with multiple layers, the number of layers of the winding is not particularly limited, for example, it can also be 2 to 10 layers.

[0080] In the coil 20, the ends 2e1 and 2e2 of the insulating coated conductive wire 2 are respectively led outward from the winding portion in the X-axis direction. External terminals (not shown) can be connected to the ends 2e1 and 2e2, and the ends 2e1 and 2e2 may have regions where the insulating layer 8 is partially removed and the metal conductor 6 is exposed. In addition, the shape or leading direction of the ends 2e1 and 2e2 is not particularly limited.

[0081] When manufacturing the coil 20, the insulation coated wire 2 may be wound in a predetermined manner after the insulation layer 8 is formed. Alternatively, after the wire material consisting of only the metal conductor portion 6 is wound into a coil shape, the unfired insulation layer 8A may be formed on the surface of the metal conductor portion 6 by a dip coating method or the like. When the insulation coated wire 2 is wound after the insulation layer 8 is formed, the insulation coated wire 2 may be wound before the insulation layer 8 is fired, or the insulation coated wire 2 may be wound after the insulation layer 8 is fired. That is, the insulation coated wire 2 having the unfired insulation layer 8A may be wound to form a coil shape, or the insulation coated wire 2 having the fired inorganic insulation layer 8B may be wound to form a coil shape.

[0082] like Figure 3 The coil 20 shown can be assembled into the circuit as an air-core coil, or can be used in combination with a magnetic core. When the coil 20 is applied to an electronic component having a magnetic core, the coil 20 is formed by winding the insulating coated wire 2 on a winding frame made of a non-magnetic material, or the winding frame and the magnetic core can be combined. In addition, the magnetic core can be inserted into the inner circumferential wall of the coil 20, or the coil 20 can be formed by winding the insulating coated wire 2 on the outer surface of the magnetic core. Furthermore, the coil 20 can also be used by being buried inside a pressed powder core containing magnetic powder and resin. In particular, the insulating coated wire 2 has high heat resistance, so the coil 20 can be buried inside a magnetic core composed of a sintered body. For example, Figure 4 2 is a cross-sectional view showing an example of an electronic component including the coil 20 .

[0083] Figure 4The electronic component 100 shown has a magnetic core 40, a coil 20 present inside the magnetic core, and an external terminal not shown. The magnetic core 40 is a sintered body of magnetic powder and does not contain resin components such as epoxy resin, phenolic resin or silicone resin. The shape and size of the magnetic core 40 are not particularly limited. In addition, the magnetic powder of the magnetic core 40 is not particularly limited either, for example, it is preferred to use soft magnetic metal powder. As soft magnetic metal powder, for example, Fe-Ni alloy powder, Fe-Si alloy powder, Fe-Si-Cr alloy powder, Fe-Co alloy powder, Fe-Si-Al alloy powder, Fe-based amorphous alloy powder and Fe-based nanocrystalline alloy powder can be cited. The particle size of the magnetic powder is not particularly limited, for example, the average particle size of the magnetic powder can be set to be greater than 1μm and less than 100μm.

[0084] In the case where the magnetic powder is composed of soft magnetic metal particles as described above, an insulating film formed by oxidation of the metal surface or a coating containing an inorganic compound can also be formed on the surface of each soft magnetic metal particle. In this case, adjacent soft magnetic metal particles are in contact with each other via the insulating film, or are joined via a grain boundary phase containing Si-based oxides. In other words, there is no organic component such as resin between the particles. The average thickness of the insulating film formed on the surface of the soft magnetic metal particles is not particularly limited, and for example, it can also be set to be more than 5nm and less than 200nm.

[0085] In addition, the magnetic powder of the magnetic core 40 may also be a mixed powder of two or more particle groups having different particle compositions and / or particle sizes. For example, a magnetic powder may be a mixture of Fe-Si alloy particles having a particle size of 25 μm or more and pure Fe particles having a particle size of less than 5 μm.

[0086] In the electronic component 100, the coil 20 exists inside the magnetic core 40 composed of a sintered body, and the periphery of the coil 20 is covered with sintered magnetic powder. In addition, the sintered magnetic powder exists not only around the coil 20, but also between the windings of the coil 20. In this way, when the coil 20 exists inside the sintered body, in the insulating coated wire 2, the insulating layer 8 exists as the inorganic insulating layer 8B after sintering. That is, inside the magnetic core 40, the windings of the coil 20 (between the metal conductor parts 6 adjacent in the Z direction) are insulated by the inorganic insulating layer 8B.

[0087] In addition, the ends 2e1 and 2e2 of the insulating coated wire 2 constituting the coil 20 are respectively led out from the inside of the magnetic core 40 to the outer surface of the magnetic core 40, and are electrically connected to the external terminals existing on the outer surface of the magnetic core 40. In the connection portion between the ends 2e1 and 2e2 and the external terminals, the inorganic insulating layer 8B is partially removed, and the metal conductor portion 6 is in direct contact with the external terminals.

[0088] The manufacturing method of the electronic component 100 is not particularly limited. For example, the magnetic core 40 can also be manufactured by press molding. First, the coil 20 is set in the cavity of the molding die. Then, the composite material obtained by mixing the magnetic powder and the binder is filled into the cavity, and the cavity is pressurized at a specified pressure. Thereafter, the magnetic core 40 can be obtained as a sintered body containing the coil 20 by sintering the molded body in which the coil 20 is embedded. The sintering conditions are not particularly limited as long as they are set to the conditions for sintering the magnetic powder. For example, the sintering temperature can be set to above 500°C and below 900°C, and the sintering time can be set to 0.5 hours to 10 hours. In addition, a debinding treatment can also be performed before sintering.

[0089] In addition, in the manufacture of the electronic component 100, the coil 20 having the inorganic insulating layer 8B may be embedded in the molded body. Alternatively, the coil 20 having the unfired insulating layer 8A may be embedded in the molded body, and the unfired insulating layer 8A may be fired at the same time as the magnetic core 40 is fired. From the viewpoint of production efficiency, it is preferred to fire the insulating layer 8 when the magnetic core 40 is fired, as in the latter. In short, inside the sintered magnetic core 40, the inorganic insulating layer 8B of the coil 20 does not substantially contain organic matter.

[0090] Here, a magnetic core composed of a sintered body generally has a higher density than a powder magnetic core composed of magnetic powder and resin. Therefore, a magnetic core composed of a sintered body generally has a higher magnetic permeability than a powder magnetic core composed of magnetic powder and resin.

[0091] However, in the case of forming a coil using an existing conductive wire having an insulating coating containing a resin (e.g., polyamide-imide resin, polyimide resin, epoxy resin, or polyurethane resin), if the magnetic core is sintered as described above, the insulating coating on the surface of the coil will be burned. Alternatively, the resin in the insulating coating on the surface of the coil is carbonized, so the resistance of the insulating coating is significantly reduced. As a result, the insulation between the conductive wires in the coil is damaged. That is, the windings of the coil are short-circuited, and the number of turns of the conductive wire in the coil is reduced. As a result, even if the magnetic core is sintered, the inductance is reduced. In contrast, in the case of using a coil 20 composed of an insulating coated conductive wire 2, the insulating layer 8 becomes an inorganic insulating layer 8B with high heat resistance during the sintering process of the magnetic core 40, so that even after the magnetic core 40 is sintered, the insulation between the windings in the coil 20 can be maintained. That is, in the electronic component 100, both "a magnetic core 40 composed of a sintered body with high magnetic permeability" and "a coil 20 with insulation between windings maintained" are taken into account. In addition, it is possible to suppress the contact between the magnetic powder around the coil 20 and between the windings and the metal conductor portion 6 of the wire 2. As described above, since the coil 20 has high heat resistance, the magnetic core 40 can be sintered in a state where the coil 20 is embedded, and the filling rate of the magnetic powder in the magnetic core 40 is increased by sintering the magnetic core 40. As a result, the electronic component 100 can obtain a higher inductance than an electronic component composed of a powder core containing magnetic powder and resin.

[0092] (Summary of the First Embodiment)

[0093] The insulated coated conductor 2 of the present embodiment includes a metal conductor portion 6 containing Cu and an insulating layer 8 covering the metal conductor portion 6. The insulating layer 8 contains Si, Ti and oxygen, and the ratio of the Ti content in the insulating layer 8 to the total content of Si and Ti (Ti / (Si+Ti)) is 2.5 at% or more and 50 at% or less.

[0094] The insulating layer 8 is formed by a sol-gel method, and Ti / (Si+Ti) hardly changes before and after firing. That is, the insulated coated wire 2 in a state where the insulating layer 8 is fired has a metal conductor portion 6 containing Cu and an inorganic insulating layer 8B covering the metal conductor portion 6. The insulating layer 8B contains an oxide containing Si and Ti, and the ratio of the Ti content in the insulating layer 8B to the total content of Si and Ti (Ti / (Si+Ti)) is 2.5 at% or more and 50 at% or less.

[0095] Since the insulating layer 8 (8A, 8B) satisfies 2.5 at% ≤ (Ti / (Si+Ti)) ≤ 50 at%, the uniformity of the insulating layer 8 can be improved. In addition, since the insulating layer 8 (8A, 8B) satisfies 2.5 at% ≤ (Ti / (Si+Ti)) ≤ 50 at%, even after heating at a high temperature of 500°C or more, a high insulation resistance can be obtained by the insulating layer 8. That is, the insulated coated wire 2 can obtain high heat resistance by having the insulating layer 8 (8A, 8B) satisfying the specified Ti / (Si+Ti).

[0096] In the insulated coated conductor 2, the average thickness T of the insulating layer 8 is Ave It is preferably 1 μm or more and 220 μm or less. In particular, the average thickness T2 of the inorganic insulating layer 8B after firing is Ave Preferably, it is 1 μm or more and 200 μm or less. By satisfying the above average thickness, the heat resistance of the insulated coated wire 2 is further improved. In addition, when the insulated coated wire 2 is applied to a coil such as an inductor, by satisfying the above average thickness, the space factor of the conductor (metal conductor portion 6) can be sufficiently ensured in the coil cross section. As a result, the reduction in inductance caused by the increase in leakage magnetic flux can be suppressed.

[0097] (Second Embodiment)

[0098] Hereinafter, one embodiment of the present disclosure will be described with reference to the drawings. Matters not particularly described are the same as those of the first embodiment.

[0099] like Figure 3 As shown, the coil 20 of this embodiment has a conductor 2 wound helically along the Z axis. The conductor 2 may be the insulating coated conductor 2 of the first embodiment. In addition, a part of the conductor 2 may be the same as a part of the insulating coated conductor 2 of the first embodiment.

[0100] constitute Figure 3 The conductor 2 of the coil 20 is a round wire, such as Figure 1 and Figure 2 However, the shape of the wire 2 is not particularly limited, and the wire 2 may also have an elliptical, rectangular, square or other polygonal cross-sectional shape.

[0101] like Figure 1 and Figure 2 As shown, the wire 2 has a metal conductor portion 6 and an insulating coating (8A, 8B) covering the metal conductor portion 6. The insulating coating (8A, 8B) may also be the insulating layer 8 of the first embodiment. In addition, the structure of a part of the insulating coating (8A, 8B) may also be the same as the structure of a part of the insulating layer 8 of the first embodiment.

[0102] The insulating coating (8A, 8B) includes an insulating material containing a predetermined inorganic element M. Specifically, the inorganic element M is one or more elements selected from Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni and Mg. The number of types of the inorganic element M contained in the insulating material is not particularly limited, and for example, it can be set to 1 to 3. In addition, from the viewpoint of extremely low decomposability at room temperature after becoming an oxide and high insulation, the inorganic element M of the insulating material is preferably one or more elements selected from Si, Al, Zr, Zn, Ti, Nb, Ta and B.

[0103] The insulating coating (8A, 8B) of the conductor 2 is formed by a sol-gel method. When the insulating coating is formed by the sol-gel method, the specifications (size and material, etc.) of the metal conductor part 6 remain unchanged before and after firing, but the state of the insulating coating changes. In the present embodiment, the insulating coating before firing is referred to as "unfired insulating layer 8A", and the insulating coating after firing is referred to as "inorganic insulating layer 8B". In the unfired insulating layer 8A, the inorganic element M is contained in the organic matter, while the inorganic insulating layer 8B contains an oxide composed of the inorganic element M. Below, the characteristics of the unfired insulating layer 8A and the inorganic insulating layer 8B are described in detail together with an example of a method for forming the insulating coating.

[0104] When the insulating coating is formed by the sol-gel method, first, a coating solution is prepared using a raw material containing an inorganic element M. As the raw material containing the inorganic element M, a liquid organic compound that becomes an oxide after calcination can also be used. As such an organic compound, for example, alkoxides and chelate compounds can be cited. Below, the organic compound containing the inorganic element M is exemplified.

[0105] When Si is contained as the inorganic element M, the Si source is the same as that in the first embodiment.

[0106] When Ti is contained as the inorganic element M, the Ti source is the same as that in the first embodiment.

[0107] Examples of the Zr source when Zr is contained as the inorganic element M include zirconium alkoxides such as zirconium tetramethoxide, zirconium tetraethoxide, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, and zirconium tetra-n-butoxide. When the Zr source is added to the coating liquid, one zirconium alkoxide may be used, or two or more zirconium alkoxides may be used in combination.

[0108] As Al sources when Al is included as the inorganic element M, aluminum alkoxides such as aluminum ethoxide, aluminum isopropoxide, and aluminum sec-butoxide, and aluminum chelates such as aluminum triacetylacetonate, aluminum triethylacetoacetate, and monoacetylacetonate bis(ethylacetoacetate)aluminum, can be exemplified. When an Al source is added to the coating solution, one aluminum alkoxide or aluminum chelate can be used, or two or more aluminum alkoxides or / and aluminum chelates can be used in combination.

[0109] The case where an element other than the above-mentioned elements is included as the inorganic element M is described. As a Zn source, zinc alkoxides such as zinc ethoxide may be used, as a Nb source, niobium alkoxides such as pentaethoxyniobium may be used, as a Ta source, tantalum alkoxides such as pentaethoxytantalum may be used, as a B source, boric acid alkoxides such as tributoxyborane may be used, as a Ni source, nickel alkoxides such as nickel ethoxide may be used, and as a Mg source, magnesium alkoxides such as magnesium ethoxide may be used. When a Zn source, Nb source, Ta source, B source, Ni source or Mg source as described above is added to the coating solution, two or more alkoxides or / and chelate compounds may be used in combination.

[0110] Furthermore, in order to adjust the viscosity of the coating liquid, an organic solvent may be appropriately added to the coating liquid in addition to the raw material containing the inorganic element M. The composition of the inorganic insulating layer 8B finally generated and the content of the inorganic element M in the insulating coating (8A, 8B) can be controlled by the ratio of the raw materials (the raw materials containing the inorganic element M) in the coating liquid.

[0111] Next, the unfired insulating layer 8A is formed by, for example, a dip coating method using the above-mentioned coating liquid. The wire material consisting only of the metal conductor portion 6 before being dipped in the coating liquid can be manufactured by a known method or prepared by purchasing a commercially available product. The wire material consisting only of the metal conductor portion 6 can also be dipped in the coating liquid before being processed into a coil shape. Alternatively, the wire material consisting only of the metal conductor portion 6 can be pre-wound into a coil shape and then the coiled wire material can be dipped in the coating liquid.

[0112] The thickness tA of the unfired insulating layer 8A and the thickness tB of the inorganic insulating layer 8B can be controlled by the immersion time in the coating liquid, the number of immersions in the coating liquid, and the like.

[0113] The unfired insulating layer 8A after drying ( Figure 1) is a coating of a dry gel of organic matter such as a polymer compound of an organic compound derived from a raw material. It is believed that the molecular structure of the organic matter contained in the unfired insulating layer 8A varies depending on the type of raw material (organic compound) used in the coating solution and the degree of drying. The structural analysis of the organic matter contained in the unfired insulating layer 8A is sometimes difficult, and the molecular structure is not particularly limited, but the organic matter in the unfired insulating layer 8A contains at least an inorganic element M. As mentioned above, the inorganic element M is one or more elements selected from Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni and Mg, and is preferably one or more elements selected from Si, Al, Zr, Zn, Ti, Nb, Ta and B. In addition, the organic matter in the unfired insulating layer 8A contains, in addition to the inorganic element M, C (carbon), H (hydrogen) and O (oxygen), which are general constituent elements of organic matter.

[0114] Here, "organic matter containing inorganic element M" refers to an organic compound containing a bond via inorganic element M in the molecular chain. That is, the inorganic element M is present in the molecular skeleton of the organic compound, and examples of the bond via inorganic element M include MO, MH, M-OH, M-OR (R is an organic functional group), etc. As mentioned above, it is not easy to analyze the structure of the organic matter in the unfired insulating layer 8A, so the bond via inorganic element M is not particularly limited, but it is considered that at least MO is contained in the organic matter of the unfired insulating layer 8A.

[0115] The unfired insulating layer 8A may contain oxides generated by decomposition of part of the organic matter. The oxides generated by decomposition of the organic matter are oxides containing an inorganic element M (MO X ) That is, the unfired insulating layer 8A may be a composite body containing an organic substance and an inorganic compound.

[0116] As mentioned above, it is believed that the inorganic element M exists in the skeleton of the polymer compound in the unfired insulating layer 8A, and a part of the inorganic element M can exist as an oxide. The inorganic element M contained in the unfired insulating layer 8A can be specified by point analysis using EDS or WDS. The point analysis of EDS or WDS is preferably implemented in at least 10 cross sections of the unfired insulating layer 8A, and its average value is calculated. If the total of the elements detected by the point analysis is set to 100at%, the total content of the inorganic element M in the unfired insulating layer 8A is not necessarily limited, but for example, it is preferably more than 1at% and less than 10at%.

[0117] The average thickness T1 of the unfired insulating layer 8A Ave The thickness tA of the unfired insulating layer 8A is preferably within a range of 1.5 μm to 220 μm. AveThe average thickness is preferably within the range of ±10%, preferably within the range of ±10%, Ave In other words, the tolerance of the thickness tA of the unfired insulating layer 8A is preferably within the range of ±10%, and more preferably within the range of ±5%.

[0118] When calculating the average thickness T1 of the unfired insulating layer 8A Ave When the conductor 2 is subjected to the analysis, it is preferred to analyze at least 10 cross sections of the conductor 2, and it is preferred to measure the thickness tA of the unfired insulating layer 8A at 10 or more locations in each cross section. In addition, the maximum thickness t1 of the unfired insulating layer 8A is determined by the measurement. MAX and minimum thickness t1 MIN , based on T1 Ave 、t1 MAX and t1 MIN The tolerance (%) of the thickness tA of the unfired insulating layer 8A can be calculated. Specifically, t1 MAX Relative to T1 Ave Deviation (t1 MAX -T1 Ave ) and t1 MIN Relative to T1 Ave Deviation (t1 MIN -T1 Ave ), by dividing the deviation with the larger absolute value by T1 Ave The tolerance of the thickness tA is calculated. That is, "F1=(|t1 MAX -T1 Ave | / T1 Ave )×100” and “F2=(|t1 MIN -T1 Ave | / T1 Ave )×100”, and the larger of F1 and F2 is used as the tolerance (%) of thickness tA.

[0119] When the unfired insulating layer 8A is formed before the wire 2 is processed into a coil shape (before the wire 2 is wound), the wire 2 may be wound after the unfired insulating layer 8A is sintered by heat treatment, or the unfired insulating layer 8A may be sintered by heat treatment after the wire 2 is wound.

[0120] An organic substance containing an inorganic element M exists in the unfired insulating layer 8A, but the organic substance is decomposed and oxidized by heat treatment to form a coating of an oxide containing the inorganic element M. That is, the inorganic element M in the organic substance remains in the inorganic insulating layer 8B as an oxide.

[0121] As described above, the inorganic insulating layer 8B after firing includes an oxide containing at least the inorganic element M, and preferably contains substantially no organic matter.

[0122] As described above, the inorganic element M constituting the oxide of the inorganic insulating layer 8B is one or more elements selected from Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni, and Mg, and is preferably one or more elements selected from Si, Al, Zr, Zn, Ti, Nb, Ta, and B from the viewpoint of extremely low decomposition at room temperature and ability to maintain high insulation. The inorganic insulating layer 8B may contain carbides, nitrides, and unavoidable impurities in addition to the above-mentioned oxides, but the content of the oxide in the inorganic insulating layer 8B is preferably 50 mol% or more, and more preferably 75 mol% or more.

[0123] In the inorganic insulating layer 8B, the oxide containing the inorganic element M is represented by the simple formula “MO X ” indicates. If the total content of elements other than oxygen contained in the inorganic insulating layer 8B is set to 100 at %, the total content of the inorganic element M in the inorganic insulating layer 8B is preferably 50 at % or more, and more preferably 75 at % or more.

[0124] In addition, the inorganic insulating layer 8B may contain one or more elements selected from P, Bi, Ba, Ca, V, Ge, and Te. These elements may be intentionally added to the inorganic insulating layer 8B or may be contained in the inorganic insulating layer 8B as impurities.

[0125] The oxide of the inorganic insulating layer 8B preferably contains Si as the inorganic element M. When the oxide of the inorganic insulating layer 8B contains Si, it may contain one or two inorganic elements M in addition to Si. As the inorganic element M added together with Si, it is preferably one or more selected from Ti, B and Al. For example, the oxide of the inorganic insulating layer 8B is preferably Si-Ti-O X 、Si-BO X or Si-B-Al-O X .

[0126] The oxide in the inorganic insulating layer 8B is Si-Ti-O X In the case of the above, the ratio of the content of Ti in the inorganic insulating layer 8B to the total content of Si and Ti is preferably 2.5 at% or more and 50 at% or less, more preferably 5.0 at% or more and 40 at% or less, and further preferably 7.5 at% or more and 25 at% or less. By setting the ratio of the content of Ti to the total content of Si and Ti to 2.5 at% or more, the resistance of the inorganic insulating layer 8B can be further increased. In addition, by setting the ratio of the content of Ti to the total content of Si and Ti to 50 at% or less, Ti can be effectively captured in the Si-O skeleton.

[0127] The oxide of the inorganic insulating layer 8B is Si-BO X In the case of the above, the ratio of the content of B in the inorganic insulating layer 8B to the total content of Si and B is preferably 1 at% to 20 at%, and more preferably 5 at% to 15 at%. By setting the ratio of the content of B to the total content of Si and B to the above range, when the wire 2 is exposed to a high temperature environment of 300°C or more, a local softening portion is generated in the insulating coating, and the thermal stress generated between the metal conductor portion 6 and the insulating coating can be alleviated.

[0128] The oxide in the inorganic insulating layer 8B is Si-B-Al-O X In the case of Si-B-Al-O, the ratio of the content of B in the inorganic insulating layer 8B to the total content of Si, B and Al is preferably 1 at% to 20 at%, more preferably 5 at% to 15 at%. In addition, the ratio of the content of Al in the inorganic insulating layer 8B to the total content of Si, B and Al is preferably 0.5 at% to 5 at%, more preferably 1 at% to 3 at%. X The B content and / or Al content in the above range is set so that when the wire 2 is exposed to a high temperature environment of 300° C. or above, a local softening area is generated in the insulation coating, which can alleviate the thermal stress generated between the metal conductor part 6 and the insulation coating.

[0129] The composition of the oxide in the inorganic insulating layer 8B and the content of the inorganic element M can be calculated, for example, by point analysis using EDS or WDS. The point analysis of EDS or WDS is preferably performed in at least 10 cross sections of the inorganic insulating layer 8B, and the average value thereof is calculated. In addition, the composition of the oxide in the inorganic insulating layer 8B can be controlled based on the ratio of the raw materials (organic compounds such as alkoxides and chelate compounds) in the coating solution.

[0130] In addition, the inorganic insulating layer 8B is preferably a film with high density and homogeneity, rather than a form in which granular or / and fibrous substances are deposited. For example, in the inorganic insulating layer 8B, the inorganic elements M and oxygen constituting the oxide are preferably uniformly distributed rather than locally unevenly distributed. In addition, when the oxide of the inorganic insulating layer 8B contains two or more inorganic elements M, it is preferred that the presence sites of the inorganic elements M are repeated.

[0131] The distribution of inorganic elements M and oxygen in the inorganic insulating layer 8B can be confirmed, for example, by using the mapping analysis of EDS or WDS. In the mapping image obtained by the analysis, the concentration of the measured object element (inorganic element M, oxygen) is expressed as the brightness corresponding to the integrated intensity of the detection peak (the peak of the characteristic X-ray detected at each measurement point), and it is possible to visually confirm whether the measured object element is uneven. In addition, the data of the brightness or integrated intensity obtained by the mapping analysis are used as a whole, and the average value, standard deviation and coefficient of variation (standard deviation / mean value) of the whole are calculated, so that the distribution of the measured object element can be quantitatively evaluated. For example, in the inorganic insulating layer 8B, the coefficient of variation of the distribution of each inorganic element M and the coefficient of variation of oxygen distribution are preferably less than 0.5.

[0132] As described above, in the inorganic insulating layer 8B, the oxide containing the inorganic element M is a main phase, and the main phase is preferably uniformly dispersed.

[0133] The average thickness T2 of the inorganic insulating layer 8B Ave The average thickness T2 of the inorganic insulating layer 8B is not necessarily limited, but is preferably 1 μm or more and 200 μm or less. Ave By setting the average thickness T2 of the inorganic insulating layer 8B to 1 μm or more, the insulation of the coating can be further improved. Ave By setting the thickness to 200 μm or less, a sufficient space factor of the metal conductor portion 6 in the cross section of the coil 20 can be ensured, and a decrease in inductance due to an increase in leakage magnetic flux can be suppressed.

[0134] In addition, the variation of the thickness tB of the inorganic insulating layer 8B is preferably within the range of the average thickness T2 Ave The average thickness is preferably within the range of ±10%, preferably within the range of ±10%, Ave In other words, the tolerance of the thickness tB of the inorganic insulating layer 8B is preferably within the range of ±10%, and more preferably within the range of ±5%. The average thickness T2 of the inorganic insulating layer 8B is Ave The tolerance of the thickness tB of the inorganic insulating layer 8B may be calculated by the same method as that of the unfired insulating layer 8A.

[0135] The coil 20 of this embodiment can also be used by being buried inside a powder core containing magnetic powder and resin. However, the coil 20 of this embodiment has high heat resistance, so the coil 20 is particularly preferably buried inside a magnetic core composed of a sintered body. For example, Figure 4 It is a cross-sectional view showing an example of a magnetic component including the coil 20 .

[0136] Figure 4The magnetic component 100 shown has a magnetic core 40, a coil 20 existing inside the magnetic core 40, and an external terminal not shown. The magnetic component 100 may also be the electronic component 100 of the first embodiment. In addition, the structure of a part of the magnetic component 100 may also be the same as the structure of a part of the electronic component 100 of the first embodiment.

[0137] When the coil 20 of the present embodiment is used, the magnetic core 40 can be sintered while the coil 20 is embedded. By sintering the magnetic core 40, the filling rate of the magnetic powder in the magnetic core 40 is increased. As a result, the magnetic permeability of the magnetic core 40 is greatly improved, so that in the magnetic component 100, a higher inductance can be obtained compared to the existing magnetic component composed of a pressed powder core containing magnetic powder and resin. In addition, Figure 4 The illustrated magnetic component 100 can be used as an inductor in a variety of circuits.

[0138] (Summary of Second Embodiment)

[0139] The coil 20 of this embodiment has a wound conductor 2 having a metal conductor portion 6 containing Cu and an insulating coating covering the metal conductor portion. The insulating coating present on the surface of the coil 20 can be divided into an unfired insulating layer 8A and an inorganic insulating layer 8B before and after firing.

[0140] The unfired insulating layer 8A as the insulating coating before firing contains an organic substance containing one or more inorganic elements M selected from Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni and Mg. When the coil 20 having the unfired insulating layer 8A as described above is heated at a temperature of 300°C or above, a coating (inorganic insulating layer 8B) containing an oxide of the inorganic element M is formed on the surface of the metal conductor part 6. That is, in the coil 20 having the unfired insulating layer 8A, the insulation between the windings can be maintained not only before firing but also after firing. As a result, in the coil 20 having the unfired insulating layer 8A, a high inductance can be obtained after firing.

[0141] The organic matter of the unfired insulating layer 8A preferably contains at least one selected from Si, Al, Zr, Zn, Ti, Nb, Ta and B as the inorganic element M. Since the coil 20 meets the above requirements, after firing, a stable oxide coating that is extremely difficult to decompose at room temperature can be obtained, and the insulation between the windings can be maintained for a longer period of time.

[0142] The average thickness T1 of the unfired insulating layer 8A Ave The average thickness T1 of the unfired insulating layer 8A is preferably 1.5 μm or more and 220 μm or less. Ave , which can further improve the heat resistance of the coil 20.

[0143] The inorganic insulating layer 8B as the insulating coating after firing includes an oxide containing one or more inorganic elements M selected from Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni and Mg. The inorganic insulating layer 8B as described above has high resistance and can prevent short circuits between windings. That is, the coil 20 having the inorganic insulating layer 8B has high heat resistance.

[0144] The oxide of the inorganic insulating layer 8B preferably contains at least one selected from Si, Al, Zr, Zn, Ti, Nb, Ta and B as the inorganic element M. Since the coil 20 satisfies the above requirements, the oxide in the coating is difficult to decompose at room temperature, and the insulation between the windings can be maintained for a longer period of time.

[0145] The average thickness T2 of the inorganic insulating layer 8B Ave The inorganic insulating layer 8B has the above average thickness T2. Ave , thereby further improving the heat resistance of the coil 20. In addition, the space factor of the metal conductor portion 6 in the cross section of the coil 20 can be sufficiently ensured, and the reduction in inductance accompanying the increase in leakage magnetic flux can be suppressed.

[0146] As described above, the coil 20 has high heat resistance, so when the coil 20 is applied to a magnetic component, the magnetic core 40 enclosing the coil 20 can be sintered. Figure 3 In the magnetic component 100 shown, the coil 20 having the inorganic insulating layer 8B exists inside the sintered magnetic core 40. In the magnetic component 100, the insulation between the windings can be maintained, and the filling rate of the magnetic powder can be increased compared to the pressed powder magnetic core containing magnetic powder and resin. As a result, the magnetic permeability of the magnetic core 40 is greatly improved, so in the magnetic component 100, a higher inductance than before can be obtained.

[0147] The above describes the embodiments of the present disclosure, but the present disclosure is not necessarily limited to the above embodiments, and various changes can be made within the scope of the main purpose of the present disclosure. In addition, the "insulated coated conductor" described below can also be read as "conductor", and the "insulating layer 8" can also be read as "insulating coating (8A, 8B)".

[0148] For example, as mentioned above, the cross-sectional shape of the insulating coated wire is not particularly limited, and may be Figure 5AThe flat wire-shaped insulated coated wire 2α shown in the figure has a substantially rectangular cross-sectional shape. In the case of a flat wire such as the insulated coated wire 2α, the width Wx (long side width) of the metal conductor portion 6 in the X-axis direction is preferably, for example, 0.1 mm or more and 2.5 mm or less, and the width Wz (short side width) of the metal conductor portion 6 in the Z-axis direction is preferably, for example, 0.1 mm or more and 1.0 mm or less. The above dimensions are suitable ranges when the insulated coated wire 2α is applied to a coil such as an inductor, and the dimensions of the metal conductor portion 6 in the flat wire are not particularly limited regardless of the application.

[0149] Figure 6 The coil 20α shown is used Figure 5A An example of a coil of a flat wire-shaped insulated coated conductor 2α is shown. Figure 6 As shown, in the coil 20α, an edgewise winding method is adopted, and the insulating coated wire 2α is formed with a long side width ( Figure 5A The winding method when using the flat wire-shaped insulated coated conductor 2α is not limited to Figure 6 , a flat winding method can also be used. In the case of a flat winding method, the long side width ( Figure 5A The insulating coated wire 2α is wound so that the direction Wx) shown in the figure coincides with the Z axis (winding axis). When a flat-wire-shaped insulating coated wire 2α is used, the number of turns of the insulating coated wire 2α is not particularly limited and may be appropriately determined according to desired coil characteristics.

[0150] In addition, the metal conductor portion 6 may also have two or more regions with different compositions. Figure 5B The insulated coated conductor 2β shown in FIG. 1 has a main body 6a and a metal coating 6b. Figure 5B In the embodiment, the insulated coated conductor 2β is a round wire having a circular cross-sectional shape, but in the Figure 5A In the case of the flat wire shown in FIG. 1 , the metal conductor portion 6 may also include a main body portion 6a and a metal coating layer 6b. The metal coating layer 6b is a layer composed of a metal component covering the main body portion 6a, and may be formed by electroplating, vapor deposition, or the like. In addition, the metal coating layer 6b may also have a structure in which two or more plating layers are stacked. In addition, in the case where the metal conductor portion 6 includes the metal coating layer 6b, the insulating layer 8 covers the surface of the metal coating layer 6b and is located at the outermost side of the insulating coated wire 2β. By forming the metal coating layer 6b between the main body portion 6a of the metal conductor portion 6 and the insulating layer 8, it is possible to improve the flexibility of the insulating coated wire 2β.

[0151] exist Figure 5BIn the case of the insulated coated conductor 2β shown in the figure, Cu may be contained in either the main body 6a or the metal coating 6b, or in both the main body 6a and the metal coating 6b. For example, the main body 6a may be made of pure copper or a copper alloy (that is, the main component of the main body 6a may be made of Cu), and a metal coating 6b containing one or more selected from Ni, Cr, Al, Ag, and Zn may be formed on the surface of the main body 6a. Alternatively, the main body 6a may be made of pure Al or an Al alloy, and a metal coating 6b containing Cu may be formed on the surface of the main body 6a (so-called copper-coated aluminum wire).

[0152] The average thickness of the metal coating layer 6b is not particularly limited, and can be, for example, 10 μm or more and 150 μm or less. Figure 1 The average diameter D or Figure 5A The widths Wx and Wz are the same size.

[0153] Example

[0154] Hereinafter, the present disclosure will be described based on more detailed examples, but the present disclosure is not limited to these examples.

[0155] (Experiment 1)

[0156] In Experiment 1, the insulated coated wires involved in Samples A1 to A17 were manufactured in the following order. First, trimethoxysilane as a Si source and titanium tetra-n-butoxide as a Ti source were prepared, and a coating liquid was prepared using these raw materials. Specifically, in Samples A2 to A16, the ratio of the Si source and the Ti source was controlled so that the Ti / (Si+Ti) ratio in the insulating layer became the value shown in Table 1. In addition, only the Si source was added to the coating liquid of Sample A1, and only the Ti source was added to the coating liquid of Sample A17.

[0157] Next, a Cu wire having an average diameter D of 500 μm was prepared, and the Cu wire was immersed in the above-mentioned coating solution for 30 seconds and allowed to stand. Thereafter, the Cu wire taken out from the coating solution was dried. During the drying process, the holding temperature was set to 100° C., and the temperature holding time was set to 30 minutes. By repeating the immersion in the coating solution and the drying process three times, an insulated coated wire having an insulating layer (unfired insulating layer) was obtained. The following evaluations were performed on the insulated coated wires before firing in each sample.

[0158] Measurement of average thickness and thickness tolerance of insulation layers

[0159] The cross section of the insulating coated wire was observed using a scanning electron microscope (SEM), and the thickness tA of the unfired insulating layer present on the surface of the Cu wire was measured. For each sample, 10 cross sections of the insulating coated wire were analyzed, and the thickness tA of the unfired insulating layer was measured at 10 locations in each cross section. The average thickness T1 was calculated from the data of the thickness tA obtained by the measurement. Ave , maximum thickness t1 MAX and minimum thickness t1 MIN In addition, "F1=(|t1 MAX -T1 Ave | / T1 Ave )×100” and “F2=(|t1 MIN -T1 Ave | / T1 Ave )×100”, the larger of F1 and F2 is used as the tolerance (%) of thickness tA.

[0160] Regarding the uniformity of the thickness of the insulating layer, samples with a thickness tolerance within a range of ±10% were judged to be good, and samples with a thickness tolerance within a range of ±5% were judged to be particularly good.

[0161] Insulation layer composition analysis

[0162] When performing cross-sectional analysis using SEM, point analysis based on EDS is performed to measure the Si content (at%) and Ti content (at%) contained in the unfired insulating layer. In addition, the point analysis is performed at least 10 locations, and the Si and Ti contents are calculated as average values. Then, based on the measurement results, the ratio of the Ti content in the unfired insulating layer to the total content of Si and Ti (Ti / (Si+Ti)) is calculated.

[0163] Determination of insulation resistance based on insulation layer

[0164] After coating, the insulation resistance (Ω) obtained from the insulation layer before firing (unfired insulation layer) was measured using HP high resistance meter 4339B. In this measurement, the unfired insulation layer corresponding to 1 / 2 of the surface was partially removed. Then, one of the measurement terminals was attached to the portion where the unfired insulation layer was removed (i.e., the portion where Cu as the metal conductor was exposed), and the other of the measurement terminals was attached to the surface of the unfired insulation layer to measure the insulation resistance. Regarding the insulation resistance of the unfired insulation layer, 1×10 7 In addition, the "ND" shown in the insulation resistance column of Table 1 means that the insulation resistance is less than 1×10 3 Ω, which means that the insulation resistance cannot be measured.

[0165] <Firing of Insulating Layer>

[0166] In the above evaluation before firing, in the samples (samples A5 to A17) whose insulation resistance can be measured, the insulation coated wire was subjected to heat treatment (firing treatment) in order to sinter the insulation layer. In the heat treatment, the holding temperature was set to 700°C and the temperature holding time was set to 1 hour. Through this heat treatment, the insulation layer was sintered, and an insulation coated wire having an inorganic insulation layer was obtained.

[0167] The average thickness and thickness tolerance of the inorganic insulating layer, component analysis of the inorganic insulating layer, and insulation resistance of the inorganic insulating layer were measured for the insulated coated wire after firing in the same manner as before firing. In addition, the appearance of the inorganic insulating layer formed after firing was inspected, and the presence or absence of cracks in the inorganic insulating layer was investigated.

[0168] Evaluation of heat resistance

[0169] The heat resistance of the insulated coated wire was evaluated based on the insulation resistance (Ω) of the inorganic insulating layer after firing and the results of the appearance inspection of the inorganic insulating layer. Specifically, when no cracks were generated and the insulation resistance was 1×10 6 Ω or more, it is judged as "good heat resistance", and if no cracks occur and the insulation resistance is 1×10 10 When Ω or more, it was judged as "particularly good heat resistance".

[0170] Table 1 shows the evaluation results of Experiment 1.

[0171] [Table 1]

[0172]

[0173] In samples A1 to A4 as comparative examples, oxide particles were confirmed to be deposited on the surface of Cu as the metal conductor part, and no continuous coating was formed. Therefore, the thickness of the coating layer was not measured for samples A1 to A4. In samples A1 to A4, the resistance value measured from the surface of the deposit was almost the same as the resistance value of the metal conductor part (Cu wire), and no coating with sufficient resistance value was formed.

[0174] In addition, in the comparative examples of samples A12 to A17, the tolerance of the thickness of the insulating layer was large and the uniformity could not be ensured. Therefore, in samples A12 to A17, the thermal stress generated during firing was not uniform, and cracks were generated in a part of the inorganic insulating layer. In other words, the insulating coated wires of samples A12 to A17 could not obtain sufficient heat resistance.

[0175] On the other hand, in the samples A5 to A11 as examples, the thickness tolerance was within the range of ±5% of the average thickness both before and after firing, and it was confirmed that a highly uniform insulating layer was formed. In addition, in the samples A5 to A11, even after heat treatment at 700°C, high insulation resistance was maintained and crack generation was suppressed. Based on this result, it was confirmed that high heat resistance can be obtained by having an insulating layer satisfying 2.5at%≤Ti / (Si+Ti)≤50at% in the insulating coated wire.

[0176] (Experiment 2)

[0177] In Experiment 2, 10 kinds of insulated coated wires with different average thicknesses of the unfired insulating layer were manufactured. In samples B1 to B9 of Experiment 2, the same coating solution as sample A6 of Experiment 1 was used, and the Ti / (Si+Ti) ratio was controlled to 5.2 at%. In addition, the average thickness of the unfired insulating layer in each sample was controlled to the value shown in Table 2 based on the number of repetitions of the coating process. The manufacturing conditions in Experiment 2 other than the above were the same as those in Experiment 1, and the same evaluation as in Experiment 1 was performed on each sample of Experiment 2. The evaluation results of Experiment 2 are shown in Table 2.

[0178] [Table 2]

[0179]

[0180] The results in Table 2 show that by setting the average thickness of the unfired insulating layer to 1 μm or more and 220 μm or less (in other words, by setting the average thickness of the inorganic insulating layer to 1 μm or more and 200 μm or less), an inorganic insulating layer having uniform and high insulation properties can be obtained.

[0181] (Experiment 3)

[0182] In Experiment 3, 15 types of air-core coils shown in Tables 3 and 4 (Examples 1 to 13 in Table 3 and Comparative Examples 1 to 2 in Table 4) were manufactured in the following order.

[0183] Examples 1 to 13

[0184] First, as a conducting wire, a flat Cu wire having a cross-sectional size of 0.65 mm×0.180 mm was prepared, and an unfired insulating layer was formed on the surface of the Cu wire by a dip coating method.

[0185] When forming the unfired insulating layer, first, a coating liquid to which a raw material containing an inorganic element M is added is prepared. Specifically, in each example, a coating liquid containing the raw materials shown below is prepared. Example 1 uses trimethylethoxysilane (Si source), Example 2 uses aluminum sec-butoxide (Al source), Example 3 uses zirconium tetra-n-propoxide (Zr source), Example 4 uses zinc ethoxide (Zn source), Example 5 uses titanium tetra-n-butoxide (Ti source), Example 6 uses pentaethoxyniobium (Nb source), Example 7 uses pentaethoxytantalum (Ta source), Example 8 uses tributoxyborane (B source), Example 12 uses nickel ethoxide (Ni source), and Example 13 uses magnesium ethoxide (Mg source). In addition, Example 9 uses a coating liquid containing trimethylethoxysilane and titanium tetra-n-butoxide, Example 10 uses a coating liquid containing trimethylethoxysilane and tributoxyborane, and Example 11 uses a coating liquid containing trimethylethoxysilane, tributoxyborane, and aluminum sec-butoxide.

[0186] Next, a flat Cu wire was immersed in the above-mentioned coating solution for 30 seconds and allowed to stand. Thereafter, the coil taken out from the coating solution was heated at 100° C. for 30 minutes to be dried. The immersion in the coating solution and the drying process were repeated three times, thereby producing a Cu wire having an unfired insulating layer.

[0187] Next, the Cu wire with the unfired insulating layer was wound into a spiral shape by edgewise winding, thereby obtaining an air-core coil with the unfired insulating layer. At this time, the number of turns of the Cu wire was set to 6.5 turns, and the inner diameter of the coil after winding was set to 2.0 mm.

[0188] Analysis of insulation coating before firing

[0189] The cross section of the wire constituting the air core coil was observed using a scanning electron microscope (SEM) to measure the thickness tA of the unfired insulating layer present on the surface of the Cu wire. For each sample, 10 cross sections of the wire were analyzed, and the thickness tA was measured at 10 locations in each cross section. The average thickness T1 of the unfired insulating layer was calculated based on the measurement results. Ave (μm). In addition, in each example, when performing cross-sectional analysis based on SEM, point analysis based on EDS was performed to identify the inorganic element M contained in the organic matter of the unfired insulating layer. In each example, it was confirmed that the inorganic element M shown in Table 3 was contained in the organic matter as expected based on the composition of the coating liquid.

[0190] Measurement of inductance L1 before firing

[0191] The inductance L1 (μH) of the air-core coil before firing was measured using an LCR meter. At this time, the measurement frequency was set to 1 MHz.

[0192] <Firing of insulation coating>

[0193] In order to sinter the unfired insulating layer, the air-core coil of each example was subjected to heat treatment (sintering treatment). During the heat treatment, the holding temperature was set to 700°C and the temperature holding time was set to 1 hour. In each example, the unfired insulating layer was sintered by the heat treatment, and an air-core coil having an inorganic insulating layer was obtained.

[0194] Analysis of insulation coating after firing

[0195] The average thickness T2 of the inorganic insulating layer in each example was measured by the same method as the analysis of the unfired insulating layer before firing. Ave In addition, when performing cross-sectional analysis based on SEM, point analysis based on EDS was performed to identify the inorganic element M contained in the oxide of the inorganic insulating layer. In each example, as expected from the composition of the coating liquid, it was confirmed that the oxide contained the inorganic element M shown in Table 3.

[0196] The amount of organic matter remaining in the inorganic insulating layer was measured using TG-DTA, and the results confirmed that in all examples, the inorganic insulating layer did not contain substantially any organic matter. In addition, EDS-based mapping analysis was performed, and the results confirmed that in each example, the inorganic element M and oxygen were repeatedly and uniformly distributed in the inorganic insulating layer, and the area ratio of the oxide containing the inorganic element M was 90% or more relative to the area of ​​the inorganic insulating layer.

[0197] In Example 9, the inorganic insulating layer comprises Si-Ti-O X The inorganic insulating layer contains an oxide represented by Si-BO, and the content of Ti in the inorganic insulating layer is within a range of 2.5 at % to 50 at % relative to the total content of Si and Ti. X The inorganic insulating layer contains an oxide represented by Si-B-Al-O, and the ratio of the content of B in the inorganic insulating layer to the total content of Si and B is in the range of 1 at% to 20 at%. X The represented oxide has a B content in the inorganic insulating layer of 1 at % to 20 at % inclusive with respect to the total content of Si, B and Al, and an Al content of 0.5 at % to 5 at % inclusive.

[0198] Determination of inductance L1 after firing

[0199] The inductance L2 (μH) of the air-core coil after firing was measured using an LCR meter in the same manner as before firing. At this time, the measurement frequency was set to 1 MHz.

[0200] Evaluation of heat resistance of coils

[0201] The heat resistance of the coil is evaluated based on the change rate (%) of the inductance after firing. Specifically, the change rate of inductance is calculated by substituting the inductance L1 before firing and the inductance L2 after firing into the calculation formula "((L2-L1) / L1)×100". In Experiment 3, the heat resistance of the samples with an inductance change rate of -25% or more was judged as "good", and the heat resistance of the samples with an inductance change rate of -15% or more was judged as "particularly good".

[0202] Comparative Example 1 and Comparative Example 2

[0203] In Comparative Example 1, a flat Cu wire having an insulating coating made of a polyamide-imide resin was prepared, and the Cu wire was wound in an edgewise winding manner into a spiral shape, thereby manufacturing an air-core coil. The size of the conductor portion in the cross section of the Cu wire used was 0.65 mm × 0.180 mm. In addition, the number of turns of the Cu wire was set to 6.5 turns, and the inner diameter of the coil after winding was set to 2.0 mm.

[0204] In Comparative Example 2, a flat Cu wire having an insulating coating made of a polyimide resin was prepared, and the Cu wire was wound in an edgewise winding manner into a spiral shape, thereby manufacturing an air-core coil. The size of the conductor portion in the cross section of the Cu wire used was 0.65 mm × 0.180 mm. In addition, the number of turns of the Cu wire was set to 6.5 turns, and the inner diameter of the coil after winding was set to 2.0 mm.

[0205] In Comparative Examples 1 and 2, the inductance of the air-core coil manufactured by the above method is set to L1, and is measured using an LCR meter. After measuring L1, the air-core coil is heat treated at 700°C for 1 hour. In Comparative Examples 1 and 2, the inductance after the heat treatment is set to L2, and is measured using an LCR meter. In addition, when measuring L1 and L2, the measurement frequency is set to 1MHz. In Comparative Examples 1 and 2, similarly to the embodiment, the rate of change (%) of inductance after heat treatment is calculated based on the calculation formula "((L2-L1) / L1)×100", and the heat resistance of the coil is evaluated.

[0206] The evaluation results of each example of Experiment 3 are shown in Table 3, and the evaluation results of each comparative example are shown in Table 4.

[0207] [Table 3]

[0208]

[0209] [Table 4]

[0210]

[0211] As shown in Table 4, in both Comparative Examples 1 and 2, the insulating layer including the resin was burned after the heat treatment at 700° C., resulting in a short circuit between the windings. Therefore, in Comparative Examples 1 and 2, the inductance L2 after the heat treatment was significantly lower than the inductance L1 before the heat treatment.

[0212] On the other hand, as shown in Table 3, in the air-core coils of Examples 1 to 13, since the unfired insulating layer contains an organic substance containing a predetermined inorganic element M, the insulation resistance between the windings can be maintained even after the firing treatment at 700° C., and high heat resistance can be obtained. In other words, by forming an inorganic insulating layer composed of an oxide containing a predetermined inorganic element M on the surface of the air-core coil, high heat resistance can be obtained.

[0213] In particular, in Examples 1 to 11, the rate of change of inductance can be reduced compared to Examples 12 to 13. From this result, it can be seen that the heat resistance of the coil is further improved by the oxide of the inorganic insulating layer containing at least one inorganic element M selected from Si, Al, Zr, Zn, Ti, Nb, Ta and B.

[0214] (Experiment 4)

[0215] In Experiment 4, air-core coils having different average thicknesses of the insulating coating were produced as shown in Tables 5 to 15. Specifically, the average thickness of the insulating coating was controlled to the values ​​shown in Tables 5 to 15 based on the number of repetitions of the dipping step.

[0216] In Examples 1A to 1F of Table 5, the same coating liquid as that of Example 1 of Experiment 3 was used, in Examples 2A to 2F of Table 6, the same coating liquid as that of Example 2 was used, in Examples 3A to 3F of Table 7, the same coating liquid as that of Example 3 was used, in Examples 4A to 4F of Table 8, the same coating liquid as that of Example 4 was used, in Examples 5A to 5F of Table 9, the same coating liquid as that of Example 5 was used, in Examples 6A to 6F of Table 10, the same coating liquid as that of Example 6 was used, in Examples 7A to 7F of Table 11, the same coating liquid as that of Example 7 was used, in Examples 8A to 8F of Table 12, the same coating liquid as that of Example 8 was used, in Examples 9A to 9F of Table 13, the same coating liquid as that of Example 9 was used, in Examples 10A to 10F of Table 14, the same coating liquid as that of Example 10 was used, and in Examples 11A to 11F of Table 15, the same coating liquid as that of Example 11 was used.

[0217] The same evaluation as in Experiment 3 was performed in each example of Experiment 4. In Experiment 4, samples having an inductance L1 of 0.0700 μH or more before firing and an inductance change rate of -7.5% or more were judged as "particularly good". The evaluation results of Experiment 4 are shown in Tables 5 to 15.

[0218] [Table 5]

[0219]

[0220] [Table 6]

[0221]

[0222] [Table 7]

[0223]

[0224] [Table 8]

[0225]

[0226] [Table 9]

[0227]

[0228] [Table 10]

[0229]

[0230] [Table 11]

[0231]

[0232] [Table 12]

[0233]

[0234] [Table 13]

[0235]

[0236] [Table 14]

[0237]

[0238] [Table 15]

[0239]

[0240] As shown in Tables 5 to 15, in the samples where the average thickness of the unfired insulating layer was 1.5 μm or more and 220 μm or less, the inductance L1 before firing was 0.0700 μH or more, and the rate of change of the inductance after firing was -7.5%. According to the results of Experiment 4, the average thickness of the unfired insulating layer is preferably 1.5 μm or more and 220 μm or less, and the average thickness of the inorganic insulating layer is preferably 1 μm or more and 200 μm or less.

[0241] (Experiment 5)

[0242] In Experiment 5, 13 types of magnetic components (inductors) shown in Tables 16 and 17 (Example M1 to Example M11 in Table 16, Comparative Examples M1 to M2 in Table 17) were manufactured using the coils manufactured in Experiment 3. In each example and each comparative example of Experiment 5, the numbers marked on the sample numbers correspond to the sample numbers in Experiment 3. That is, in Comparative Example M1, a coil having an insulating coating of polyamide-imide resin was used in the same manner as in Comparative Example 1, and in Comparative Example M2, a coil having an insulating coating of polyimide resin was used in the same manner as in Comparative Example 2. In addition, Examples M1 to M11 used coils having an insulating coating containing an inorganic element M shown in Table 16 in the same manner as Examples 1 to 11, respectively. The wire diameter (average diameter of the Cu wire) and the inner diameter of the coil used in each example and each comparative example are the same as those in Experiment 3.

[0243] In each of the examples and comparative examples of Experiment 5, Fe-Si alloy powder was used as the magnetic powder. The average particle size of the Fe-Si alloy powder used in Experiment 5 was 30 μm, and an insulating coating composed of a composite oxide of Si and Ti with an average thickness of 50 nm was formed on the surface of each particle. In Experiment 5, the above-mentioned Fe-Si alloy powder was mixed with a silicone resin as a binder to obtain a composite material.

[0244] In each embodiment, after a coil with an unfired insulating layer is set in the cavity of the molding die, the above-mentioned composite material is filled in the cavity and pressurized. Through this molding process, a magnetic component with a coil with an unfired insulating layer buried inside the powder core is obtained. In Experiment 3, the inductance L3 (μH) of the magnetic component after molding is measured using an LCR meter. At this time, the measurement frequency is set to 1MHz.

[0245] In Experiment 5, after the inductance L3 was measured, the magnetic component was heat-treated at 700°C for 1 hour to sinter the powder core. In each example, through this heat treatment, it was confirmed that the insulation coating of the coil became an inorganic insulating layer that does not substantially contain organic matter, and the oxide of the inorganic insulating layer contained the inorganic element M shown in Table 16.

[0246] After the powder core is sintered by the above method, the inductance L4 (μH) of the sintered magnetic component is measured using an LCR meter. At this time, the measurement frequency is set to 1MHz. In Experiment 3, the sample whose inductance L4 after sintering is greater than the inductance L3 after molding (i.e., the sample satisfying L3<L4) is judged as "good". The evaluation results of Experiment 5 are shown in Tables 16 and 17.

[0247] [Table 16]

[0248]

[0249] [Table 17]

[0250]

[0251] As shown in Table 17, in Comparative Examples M1 and M2, although the filling rate of the magnetic powder was increased by sintering, the insulating coating (including the insulating coating of the resin) on the surface of the coil disappeared during the heat treatment, and the windings of the coil were short-circuited. As a result, the actual number of turns of the coil decreased after the sintering of the magnetic core, and the inductance L4 after sintering was significantly reduced compared to the inductance L3 after molding.

[0252] On the other hand, as shown in Table 16, in Examples M1 to M11 using a coil having an insulating coating (unfired insulating layer, inorganic insulating layer) containing a predetermined inorganic element M, the insulation resistance between windings based on the inorganic insulating layer is maintained even after the sintering of the magnetic core. In addition, in Examples M1 to M11, the filling rate of the magnetic powder is increased by the sintering of the magnetic core, so that an inductance L4 higher than the inductance L3 after forming can be obtained.

[0253] (Note)

[0254] The technology according to the present disclosure includes, but is not limited to, the following configuration examples.

[0255] (Note 1)

[0256] An insulated coated wire, wherein:

[0257] The invention comprises: a metal conductor part containing Cu, and an insulating layer covering the metal conductor part.

[0258] The insulating layer contains Si, Ti and oxygen,

[0259] A ratio of a Ti content in the insulating layer to a total content of Si and Ti is 2.5 at % or more and 50 at % or less.

[0260] (Note 2)

[0261] The insulated covered conductor according to Supplementary Note 1, wherein:

[0262] The insulating layer has an average thickness of 1 μm or more and 220 μm or less.

[0263] (Note 3)

[0264] An insulated coated wire, wherein:

[0265] The invention comprises: a metal conductor part containing Cu, and an inorganic insulating layer covering the metal conductor part.

[0266] The inorganic insulating layer comprises an oxide containing Si and Ti,

[0267] A ratio of a Ti content in the inorganic insulating layer to a total content of Si and Ti is 2.5 at % or more and 50 at % or less.

[0268] (Note 4)

[0269] The insulated coated wire according to Supplementary Note 3, wherein:

[0270] The inorganic insulating layer has an average thickness of 1 μm or more and 200 μm or less.

[0271] (Note 5)

[0272] A coil, wherein

[0273] A conductive wire comprising: a metal conductive portion containing Cu and an insulating layer covering the metal conductive portion;

[0274] The insulating layer includes an organic substance containing one or more inorganic elements M selected from the group consisting of Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni, and Mg.

[0275] (Note 6)

[0276] The coil according to Supplementary Note 5, wherein:

[0277] The organic substance includes, as the inorganic element M, one or more selected from Si, Al, Zr, Zn, Ti, Nb, Ta, and B.

[0278] (Note 7)

[0279] The coil according to Supplement 5 or 6, wherein:

[0280] The insulating layer has an average thickness of 1.5 μm or more and 220 μm or less.

[0281] (Note 8)

[0282] A coil, wherein

[0283] A conductive wire comprising: a metal conductive portion containing Cu and an inorganic insulating layer covering the metal conductive portion;

[0284] The inorganic insulating layer includes an oxide containing one or more inorganic elements M selected from the group consisting of Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni, and Mg.

[0285] (Note 9)

[0286] The coil according to Supplementary Note 8, wherein:

[0287] The oxide includes, as the inorganic element M, one or more selected from the group consisting of Si, Al, Zr, Zn, Ti, Nb, Ta, and B.

[0288] (Note 10)

[0289] A coil according to Supplementary Note 8 or 9, wherein:

[0290] The inorganic insulating layer has an average thickness of 1 μm or more and 200 μm or less.

[0291] (Note 11)

[0292] A magnetic component, wherein

[0293] The invention comprises the coil according to any one of Supplementary Notes 5 to 10 and a magnetic core made of a soft magnetic material, wherein the coil is buried inside the magnetic core.

Claims

1. An insulated coated wire, wherein: The invention comprises: a metal conductor part containing Cu, and an insulating layer covering the metal conductor part. The insulating layer contains Si, Ti and oxygen, A ratio of a Ti content in the insulating layer to a total content of Si and Ti is 2.5 at % or more and 50 at % or less.

2. The insulated coated wire according to claim 1, wherein: The insulating layer has an average thickness of 1 μm or more and 220 μm or less.

3. An insulated coated wire, wherein: The invention comprises: a metal conductor part containing Cu, and an inorganic insulating layer covering the metal conductor part. The inorganic insulating layer comprises an oxide containing Si and Ti, A ratio of a Ti content in the inorganic insulating layer to a total content of Si and Ti is 2.5 at % or more and 50 at % or less.

4. The insulated coated wire according to claim 3, wherein: The inorganic insulating layer has an average thickness of 1 μm or more and 200 μm or less.

5. A coil, wherein: A conductive wire comprising: a metal conductive portion containing Cu and an insulating layer covering the metal conductive portion; The insulating layer includes an organic substance containing one or more inorganic elements M selected from the group consisting of Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni, and Mg.

6. The coil according to claim 5, wherein The organic substance contains, as the inorganic element M, one or more selected from the group consisting of Si, Al, Zr, Zn, Ti, Nb, Ta, and B.

7. The coil according to claim 5 or 6, wherein: The insulating layer has an average thickness of 1.5 μm or more and 220 μm or less.

8. A coil, wherein: A conductive wire comprising: a metal conductive portion containing Cu and an inorganic insulating layer covering the metal conductive portion; The inorganic insulating layer includes an oxide containing one or more inorganic elements M selected from the group consisting of Si, Al, Zr, Zn, Ti, Nb, Ta, B, Ni, and Mg.

9. The coil according to claim 8, wherein: The oxide contains, as the inorganic element M, one or more selected from the group consisting of Si, Al, Zr, Zn, Ti, Nb, Ta, and B.

10. The coil according to claim 8 or 9, wherein: The inorganic insulating layer has an average thickness of 1 μm or more and 200 μm or less.

11. A magnetic component, wherein: The invention comprises: the coil according to any one of claims 5 to 10, and a magnetic core made of a soft magnetic material, The coil is buried inside the magnetic core.

Citation Information

Patent Citations

  • Self-fusible insulation wire and its coil

    JP1991089414A